Late spontaneous resolution of persistent molar pregnancy. (15th January 2016) - Taylor, F; Short, D; Harvey, R; Winter, MC; Tidy, J; Hancock, BW; Savage, PM; Sarwar, N; Seckl, MJ; Coleman, RE
Abstract : Objective: To determine the outcome of women with persistently raised but falling human chorionic gonadotrophin (hCG) levels 6 months after surgical evacuation of a molar pregnancy. Design: An 11‐year retrospective review. Setting: The United Kingdom supra‐regional trophoblastic disease treatment centres at Weston Park Hospital (Sheffield) and Charing Cross Hospital (London). Population: Women with raised but falling serum human chorionic gonadotrophin (hCG) levels 6 months after evacuation of a molar pregnancy. Methods: Retrospective case note review of eligible women identified by the electronic databases held at each supra‐regional centre. Main outcome measures: The proportion of women that attain normal hCG levels spontaneously without chemotherapy. In addition, rates of gestational trophoblastic neoplasia (GTN), drug resistance, disease relapse and overall survival are reported. Results: Thirty‐five women with molar pregnancy and raised but falling serum hCG levels continued surveillance 6 months after evacuation. Levels of hCG in 30 of the patients (86%) fell to normal levels spontaneously. One woman defaulted follow up prior to hCG normalisation (3%) and the remaining four women (11%) were treated with chemotherapy due to a plateau or rise in serum hCG levels indicating GTN. All treated women were successfully salvaged by either first ( n = 1) or second line ( n = 2) chemotherapy or found to have persistently raised low level hCG of uncertain clinical relevance ( n = 1). No women developed relapsed disease and overall survival was 100%. Conclusions: Women with a molar pregnancy and a raised but falling hCG level beyond 6 months from uterine evacuation can be safely observed with regular hCG monitoring and can usually avoid potentially toxic chemotherapy. Tweetable abstract: Women with treated molar pregnancy may avoid chemotherapy if 6‐month hCG levels are raised but falling. Tweetable abstract: Women with treated molar pregnancy may avoid chemotherapy if 6‐month hCG levels are raised but falling.